Principles of web design - Sklar, Joel (Australia : Cengage Learning, 2015)
This text will help students plan and develop well designed websites that combine effective navigation with the balanced use of graphics, text, and colour.
Previous edition: 2011.
Includes index.
Keywords: Web sites -- Design; Computers and IT